CORRIGENDUM TO “DESIGN OF A COOLING SYSTEM FROM UNDERGROUND THERMAL ENERGY STORAGE (UTES, UNDERGROUND) THERMAL ENERGY STORAGE) BASED ON EXPERIMENTAL RESULTS” (Journal of Applied Engineering Science, 2024)
In October 2024, co-author Marcelo Rodrigo Garcia Saquicela pointed out the need to supplement his affiliation. The supplementation was necessary as the work presented in published article was conducted through the involvement and engagement of two institutions.Following a request by co-author Marcelo Rodrigo Garcia Saquicela, supported by all co-authors, the Editor-in-Chief has approved the following correction for the article published in 22(2024)2, 1203, 386-392, DOI: 10.5937/jaes0-46295:José David Barros Enríquez1*, Milton Iván Villafuerte López1, Angel Moises Avemañay Morocho1, Diego Javier Punina Guerrero2, Marcelo Rodrigo Garcia Saquicela3, 41 Faculty of industrial and production sciences, Quevedo State Technical University (Uteq), Quevedo, Ecuador2 Faculty of mechanical engineering, Polytechnic Higher School of Chimborazo (Espoch), Riobamba, Ecuador3 Faculty of engineering and applied sciences, University of the Americas (Udla) Quito, Ecuador4 Faculty of Engineering Sciences, State Technical University of Quevedo, Los Rios, Ecuador* jbarros@uteq.edu.ec